Analysis and research on water hammer protection measures based on KY PIPE for long distance pumping station water transmission engineering with pump stoppage - Zhen Zhou; Zhenwei Mu; Honghong Zhang; Mengqiang Zhang; Yuanhao Gu; Xiufu Shi; Baien Zhao (Scientific Reports)
Abstract In the process of long-distance pressurized pipeline water transmission, in addition to the problem of water hammer hazards that can easily occur in the pipeline, the safety of the pipeline before the pump also presents hidden dangers. When excessive water hammer pressure occurs in the whole pipeline, it can easily lead to pipeline leakage or even pipe bursting. In this work, we analyze the pressure head in the pipeline of a long-distance pumping station using modeling calculations from KY PIPE software, combined with data from an actual water transmission project, to study the effect of stopping the pump water hammer. The use of two-phase check valves can effectively solve the problem of pump inversion when the pump water hammer stops, and the installation of an air valve and regulating tower can effectively reduce the pressure head of the pipeline. At the same time, the negative pressure in the pipeline can be eliminated, and the installation of a water hammer relief valve can effectively reduce the volume of the bladder surge tank by 77.5%. The results show that the use of joint protection equipment in a long-distance water transmission project has a better effect on the water hammer pressure in the pipeline. It is proposed that the joint protection equipment device can effectively reduce the volume of the surge tank. This provides reference significance for similar projects.